INTERACTION OF SECONDARY AND HIGHER SCHOOLS WITH IMPROVEMENT OF PEDAGOGICAL PROFESSIONALISM AS A SYSTEM AND PROCESS - Shtelmakh, H.B. (Pedagogy of Higher and Secondary Education, 2009)
In the article interaction of average and the higher school on perfection of pedagogical professionalism as one of ways of formation of the creative person of the teacher is considered.